Instructional strategies for middle and secondary social studies : methods, assessment, and classroom management - Larson, Bruce E.; Keiper, Timothy A. (New York : Routledge, 2011)
'Written explicitly for pre-service social studies teachers, this exciting methods-based text integrates an in-depth look at seven distinct teaching strategies with appropriate management and assessment techniques. Written by veteran teacher educators Bruce E. Larson and Timothy A. Keiper, Instructional Strategies for Secondary Social Studies offers teachers a detailed description of a range of teaching techniques, from lectures to role plays to student-directed investigations. It provides a practical guide for considering when to use what strategy, how to determine that students met learning objectives with a particular strategy, and how to keep the learning environment positive. Special features include: - Clear, step-by-step descriptions of the seven categories of instructional strategies that social studies teachers need most to engage all students and promote student learning. - Practical ways to manage the learning environment and assess student learning for each of the instructional strategies. - Rich, detailed and social studies-specific examples to illustrate each concept or teaching method described. - Guidelines for deciding how each strategy might allow for diverse learners and differentiated learning environments. - Clear and concrete guidelines for setting course goals and objectives as well as writing unit plans and lesson plans. For any aspiring social studies teacher who wants to make the most informed decisions about day-to-day instructional strategies, the unique integration and contextualization of curriculum, instruction, assessment, and classroom management that this textbook offers will make this an invaluable resource' -- Provided by publisher.
Includes bibliographical references (p. [269]-281) and index.
Keywords: Social sciences -- Study and teaching (Middle school) -- Textbooks; Social sciences -- Study and teaching (Secondary) -- Textbooks; History -- Study and teaching (Middle school) -- Textbooks; History -- Study and teaching (Secondary) -- Textbooks; History teachers -- Training of -- Textbooks